Representasi Makna Denotatif dan Konotatif dalam Lirik Lagu Takaramono Karya Wacci: Kajian Semiotika Roland Barthes: The Representation of Denotative aand Connotative Meanings in the Lyrics of Wacci's Takaramono: A Roland Barthes Semiotic Study - Sony Difa Febrianda; Sri Aju Indrowaty (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study aims to analyse in depth the layers of meaning embedded in the lyrics of Wacci’s song “Takaramono” by applying Roland Barthes’ semiotic approach, which encompasses denotation, connotation, and myth formation as representations of the naturalisation of ideology within culture. This research employs a descriptive qualitative method using a content analysis approach. The research data are limited to five selected linguistic units (signs), identified based on significant lexical shifts in meaning, representations of physical metaphors, and their potential sociocultural significance. The data were collected using observation and note-taking techniques. The findings reveal a shift in meaning from the denotative to the connotative level across the five principal signs: hagemashiau (励まし合う), takaramono (宝物), senaka wo osu (背中を押す), kurayami (暗闇), and hitosuji no hikari (一筋の光). At the connotative level, these signs represent emotional solidarity, motivation, despair, and hope. At the third level of signification, the myth analysis demonstrates how the song lyrics naturalise the philosophy of contemporary Japanese society, including the myths of sympathetic collectivism, the desacralisation of material wealth, the moral obligation of emotional mutual support (giri-ninjō), and psychological resilience (ganbaru/gaman), in which abstract memories and interpersonal relationships (kizuna) are ideologically constructed as enduring spiritual “treasures.” The study concludes that the lyrics of “Takaramono” do not merely explore the melancholy of individual separation; rather, they function as a cultural medium that legitimises the importance of empathy and spiritual resilience as the social foundations for confronting the dynamics of contemporary Japanese society.